Myeloma kidney – a treatable yet often forgotten disease - Lim, Christopher Thiam Seong; Fuah, Kar Wah; Khoo, Yoong Khean (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Multiple myeloma is a blood dyscrasias that accounts of almost 10% of all hematological malignancy. The presentation of myeloma kidney is highly variable and it often presents as renal insufficiency, renal tubular dysfunction and proteinuria of various types. In Malaysia the true incidence of myeloma kidney is unknown. Often the diagnosis of myeloma kidney was missed out despite the patient has sought medical treatment early. A high index of suspicion is required when the middle to elderly age patients present with unexplained renal impairment and enlarged kidneys. We present here the presentation of a rare subtype of myeloma in a relatively young patient whereby the patient presented with nephrotic syndrome and azotemia.